Nanostructured boron agents for boron neutron capture therapy: a review of recent patents - Zhang Xiyin; Lin Yusheng; Hosmane Narayan S.; Zhu Yinghuai (Medical Review, 2023)
Boron neutron capture therapy (BNCT) is a potential radiation therapy modality for cancer, and tumor-targeted stable boron-10 (10B) delivery agents are an important component of BNCT. Currently, two low-molecular-weight boron-containing compounds, sodium mercaptoundecahydro-closo-dodecaborate (BSH) and boronophenylalanine (BPA), are mainly used in BNCT. Although both have suboptimal tumor selectivity, they have shown some therapeutic benefit in patients with high-grade glioma and several other tumors. To improve the efficacy of BNCT, great efforts have been devoted for the development of new boron delivery agents with better uptake and favorable pharmacokinetic profiles. This article reviews the application and research progress of boron nanomaterials as boron carriers in boron neutron capture therapy and hopes to stimulate people’s interest in nanomaterial-based delivery agents by summarizing various kinds of boron nanomaterial patents disclosed in the past decade.